Application of PBL by Using Manipulative Materials to Determine Students' Collaborative Abilities on Bar Diagram Materials - Susilowati, Indri; Athma Putri Rosyadi, Alfiani; Mochamad Cholily, Yus (Mathematics Education Journal, 2025)
This study aims to describe students' collaborative abilities through the application of the Problem Based Learning (PBL) model assisted by manipulative materials on bar diagram materials. The study used a descriptive qualitative approach and involved grade VII students working in several groups. Data was collected through observation, LKPD analysis, and documentation of the learning process. The results showed that PBL with manipulative materials facilitated active student involvement, role sharing, flexibility in discussions, group responsibility, and mutual respect. Interaction between students developed positively and encouraged mathematical discussion, although the quality of data analysis and interpretation still varied between groups. This research makes a conceptual contribution to understanding that the development of collaborative skills is not only determined by the structure of group work, but also by the quality of interaction and the use of manipulative materials in mathematics learning.